EKSISTENSI PEMERINTAHAN DESA DITINJAU DARI PERSPEKTIF ASAS SUBSIDIARITAS DALAM UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - Hariri, Achmad (Legality : Jurnal Ilmiah Hukum, 2018)
The existence of the Village Government in the perspective of Law Number 6 of 2014Â  concerning Villages is increasingly clear, itâ€™s because the village is given the authority to manage and regulate its own household as known as the subsidiarity principle, while independence in managing governance in regional government is known as the principle of decentralization. This authority is given to realize the vision of the life of a prosperous and independent village government. But in the implementing regulations contrary to the concepts and principles of the establishment of the Village Law, there are several norms explicitly that village authority is still intervened by the government Supra Desa (Regional Government). The purpose of this study is to analyze the existence of village government. The results of this study recommend that there is a need for synchronization and harmonization between the regulations governing village authority, namely Law number. 6 of 2014 concerning Villages, Government Regulation Number 43 of 2014 concerning Implementation Regulations of Law Number 6 Year 2014 concerning Villages, and Government Regulation Number 60 of 2014 concerning Village Funds sourced from the State Budget.